Synthesis of kaolin/sodium alginate-grafted poly(acrylic acid-co-2-acrylamido-2-methyl-1-propane sulfonic acid) hydrogel composite and its sorption of lead, cadmium, and zinc ions. (October 2015) - Zhu, Linhui; Zhang, Lili; Tang, Yaoji; Ma, Dong; Yang, Jing
A new composite, kaolin/sodium alginate-grafted poly(acrylic acid- co -2-acrylamido-2-methyl-1-propane sulfonic acid) (KL/SA- g -P(AA- co -AMPS)), was synthesized by intercalation graft polymerization of KL, SA, partially neutralized AA, and AMPS, using ammonium persulfate as an initiator and N, N ′-methylenebisacrylamide as a cross-linker. The composite was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis. Possible mechanisms for the process of intercalation graft polymerization were speculated. The composite was used for the removal of heavy metal ions from aqueous solutions. Sorption behavior of heavy metal ions such as lead (Pb 2+ ), cadmium (Cd 2+ ), and zinc (Zn 2+ ) on (KL/SA- g -P(AA- co -AMPS) was investigated. Maximal adsorption capacities for Pb 2+, Cd 2+, and Zn 2+ ions were 834.7, 69.9, and 139.8 mg g −1, respectively. It was found that the adsorption of Pb 2+ and Zn 2+ ions was in agreement with the Freundlich model, whereas that of Cd 2+ ion was consistent with both Langmuir and Freundlich models. Mechanisms for the adsorption process were also discussed. It indicated that chelation played an important role for the adsorption of Pb 2+ ions, while ion exchange was decisive for the adsorption of Zn 2+ and Cd 2+ ions. It has been concluded that KL/SA- g -P(AA- co -AMPS) hydrogel composite offered excellent potential for the removal of heavy metal ions from contaminated water. In addition, the hydrogel composite could be regenerated and reused in wastewater treatment.